Multigenerational exposure of populations of Oppia nitens to zinc under pulse and continuous exposure scenarios. (27th February 2019) - Jegede, Olukayode O.; Hale, Beverley A.; Siciliano, Steven D.
Abstract: Current soil remediation guidelines for metals reflect single‐generation laboratory studies, but in the field, organisms are exposed to metals for more than one generation. The present study assessed the multigenerational effect of zinc (Zn) on Oppia nitens under a pulse or continuous exposure scenario. Synchronized adult mites (parents) were exposed to 6 concentrations of Zn in a field soil. For the pulse exposure, juveniles of parent mites from 3 of the 6 concentrations (105, 158, 237, 335, 553, and 800 mg/kg) were kept in clean media and reared until the third generation. At every generation, the sensitivity of the mites to Zn was tested in a dose–response manner. For the continuous exposure, the mites produced from the parents were re‐exposed to the same concentration as their parents. According to critical‐level estimates like the median effect concentration, all populations of the F2 and F3 generation mites in the pulse exposure were less sensitive to Zn than the parents and were protected at 250 mg/kg of Zn (Canadian Council of Ministers of the Environment [2018] soil quality guideline). However, the mite generations of the continuous exposure remained as sensitive as the parent generation and were not protected by the Zn guideline level. The Zn niche width narrowed considerably for all continuously exposed mite populations, indicating that they were more sensitive than the parent. Our results show that Zn has a deleterious multigenerational effect on continuously exposed populations of mites. Environ Toxicol Chem 2019;38:896–904. © 2019 SETAC